Fabrication of heterogeneous interface and phosphorus doping in MoS2 for efficient hydrogen evolution in both acid and alkaline electrolytes. (20th July 2021) - Xu, Qiuchen; Liu, Yanxia; Tian, Zhangmin; Shi, Yingying; Wang, Zhen; Zheng, Wenjun
Highlight: A novel P-CoS1.097 @MoS2 /CC heterostructure is employed for enhanced hydrogen evolution reaction (HER). The [BMIm] + in ionic liquid is the key to the formation of CoS1.097 @MoS2 /CC heterostructure ultrathin nanosheets. The fabrication of heterogeneous interface between CoS1.097 and MoS2 is in favor of optimizing active sites and adjusting electron distribution. The introduction of sulfur vacancies by phosphorus doping stimulates the activity on the inert plane of MoS2 . Abstract: Reasonable design of non-precious metal electrocatalysts with high catalytic activity plays a crucial role in promoting the sustainable development of hydrogen energy. Herein, to improve both the active sites and intrinsic conductivity of molybdenum disulfide (MoS2 ), a facile ionic liquid-assisted hydrothermal method and subsequent phosphorization treatment are fabricated for advanced electrochemical hydrogen evolution reaction (HER) performance. The obtained P-CoS1.097 @MoS2 /CC heterostructure exhibits a low overpotential of 98 mV and 88 mV at the current density of 10 mA cm −2 in 0.5 M H2 SO4 and 1 M KOH, respectively. The remarkable performance is due to the synergistic effects of the constructed heterogeneous interface between CoS1.097 and MoS2 as well as sulfur vacancies generated by the phosphorus doping. Therefore, fast electron transfer and large number of catalytic active sites can be achieved by means of such advantageous strategy. This research paves the way for the development of MoS2 -based catalysts through the cooperative design of doping and interface engineering toward efficient HER process. Graphical Abstract: Image, graphical abstract